Efeito da doença peridontal sobre a reatividade vascular de camundongos ateroscleróticos (APOE-/-) - Pereira, Raquel Binda (2008)
Periodontal disease was induced in mice by oral Porphyromonas gingivalis (Pg) inoculation to compare changes in vascular reactivity from animals without atherosclerosis (C57BL/6), animals with moderate atherosclerosis (ApoE) and animals with advanced atherosclerosis (ApoE D). The alveolar bone resorption was similar between the groups (P>0,05). In vitro preparations of mesenteric arteriolar bed were used to determine the vascular responses to acetylcholine, sodium nitroprusside and phenylephrine. Acetylcholine and sodium nitroprusside – induced relaxation were similar in the all groups (P>0,05). The maximal response to phenylephrine increased in the all groups, when compared to controls (C57 CT: 78,6 ± 2,7 vs C57 Pg: 92 ± 5,5; ApoE CT: 98 ± 5 vs ApoE Pg: 119 ± 6,5; ApoE D CT: 97 ± 7 vs ApoE D Pg: 120 ± 6 mmHg; P<0,05). This study demonstrates that periodontal disease increases the reactivity to phenylephrine in mice systemically healthy, with moderate atherosclerosis and with advanced atherosclerosis. Additionally to increased reactivity to phenylephrine, the periodontal disease exacerbated the systemic inflammation in mice with advanced atherosclerosis (neutrophils/lymphocytes ratio. ApoE D CT: 0,30 ± 0,04 vs ApoE D Pg: 2,37 ± 0,23, P<0,05).